2019
DOI: 10.1093/humupd/dmz015
|View full text |Cite
|
Sign up to set email alerts
|

Potential genetic causes of miscarriage in euploid pregnancies: a systematic review

Abstract: BACKGROUND Approximately 50% of pregnancy losses are caused by chromosomal abnormalities, such as aneuploidy. The remainder has an apparent euploid karyotype, but it is plausible that there are cases of pregnancy loss with other genetic aberrations that are not currently routinely detected. Studies investigating the use of exome sequencing and chromosomal microarrays in structurally abnormal pregnancies and developmental disorders have demonstrated their clinical application and/or potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 63 publications
(138 reference statements)
2
91
0
1
Order By: Relevance
“…In principle, a new L1 insertion into a lethal gene could initiate a cascade leading to fetal death, although our diploid nature limits such consequences. Many signaling pathways and genes are involved in the process of miscarriage and single gene mutations may cause spontaneous abortion [6]. Based on a study of 489 single gene knockout mouse models, White et al [88] found 29 percent of the genes to be lethal and 13 percent sublethal.…”
Section: Many Genes Are Involved In Early Embyogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…In principle, a new L1 insertion into a lethal gene could initiate a cascade leading to fetal death, although our diploid nature limits such consequences. Many signaling pathways and genes are involved in the process of miscarriage and single gene mutations may cause spontaneous abortion [6]. Based on a study of 489 single gene knockout mouse models, White et al [88] found 29 percent of the genes to be lethal and 13 percent sublethal.…”
Section: Many Genes Are Involved In Early Embyogenesismentioning
confidence: 99%
“…KIF7 (kinesin family member gene 7) was the first human gene associated with fetal lethality when it was found to cause hydrolethalus and acrocallosal syndromes [89], and since then many other candidate genes have been identified. A review of 50 human studies identified a range of possible causative gene and copy number variations (CNVs) for miscarriage, including CHRNA1 (cholinergic receptor, nicotinic, alpha polypeptide 1), DYNC2H1 (dynein, cytoplasmic 2, heavy chain 1), and RYR1 (ryanodine receptor 1), which were reported by multiple studies [6]. Several whole exome sequence analyses of euploid miscarriages have been conducted, including a study of 30 fetuses in which mutations in FGFR3 (fibroblast growth factor receptor 3), COL2A1 (collagen, type II, alpha 1), and OFD1 (oral-facial-digital syndrome 1) genes, in addition to structural variants, accounted for 10 percent of the cohort [90].…”
Section: Many Genes Are Involved In Early Embyogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The villi of RSA patients and elective pregnancy termination patients were collected, and the tissues' volume were generally not more than 1mm 3 . Fresh tissues were quickly placed into the electron microscope fixative (Servicebio), fixed at 4 °C for 2-4 h, and post-fixed in 1% osmium acid for 2h.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…The villi of RSA patients and normal abortion patients were collected, and the tissues' volume were generally not more than 1mm 3 . Fresh tissues were quickly placed into the electron microscope fixative (Servicebio), fixed at 4 °C for 2-4 h, and post-fixed in 1% osmium acid for 2 h. The samples were dehydrated in a series of gradient concentration alcohols, permeated overnight with a mixture of acetone and 812 embedding agent (SPI) (2:1), then embedded in pure 812 embedding agent and polymerized in a 60 °C oven for 48 h. Samples were cut into 60-80 nm ultrathin sections by using ultrathin slicing machine (Leica UC7).…”
Section: Transmission Electron Microscopymentioning
confidence: 99%